Resistant starch wheat increases PYY and decreases GIP but has no effect on self-reported perceptions of satiety. (1st January 2022) - Hughes, Riley L.; Horn, William F.; Wen, Anita; Rust, Bret; Woodhouse, Leslie R.; Newman, John W.; Keim, Nancy L.
Abstract: Dietary fiber has numerous health benefits, such as increasing satiety, and is regularly included in healthy dietary recommendations. However, different types and sources of fiber vary in their chemical properties and biological effects. This double-blind, randomized, placebo-controlled, crossover study investigated the effects of resistant starch type 2 (RS2) from wheat on self-reported perceptions of satiety and associated gut hormones in 30 healthy adults ages 40–65 years of age. Participants consumed rolls made using either RS2-enriched wheat flour or a wild-type flour for one week before a test day during which they ate a mixed meal containing the same roll type. Both self-reported perceptions of satiety and plasma concentrations of gut hormones were measured following the meal to assess whether the RS2-enriched wheat enhanced satiety and suppressed hunger for a longer period than the control wheat. Exploratory analysis indicated that fasting and peak concentration of peptide YY3-36 (PYY3-36 ; qfast = 0.02, qpeak = 0.02) increased, while peak concentration and iAUC of glucose-dependent insulinotropic peptide (GIP; qpeak < 0.001, qiAUC < 0.001) decreased after ingesting RS2-enriched wheat. However, self-reported perceptions of hunger or fullness using visual analog scales (VAS) did not differ following the test meal.